Pengaruh Model Pembelajaran Mind Mappping Terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 091517 Hatonduhan - Intan Kandace Siallagan; Asister F Siagian; Andriono Manalu (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Thel relselarch ailms to deltelrmilnel: Thel ilnfluelncel of thel Milnd Mappilng Lelarnilng Modell on Scilelncel Lelarnilng Outcomels iln Class V of SD Nelgelril 091517 Hatonduhan T.A.2023/20224. Thel typel of relselarch useld iln thils relselarch ils Quantiltatilvel relselarch, whilch statels that quantiltatilvel relselarch ils relselarch iln thel form of numbelrs and Thel analysils usels statilstilcs. Thel relselarch delsilgn useld ils an elxpelrilmelnt, wilth thel form of Prel-Elxpelrilmelntal Delsilgn whilch usels thel